Solo em guerra: construtivismo e subjetividade na obra tradutória de Augusto de Campos - Adilson Antônio Barbosa Júnior (2022)
This dissertation is a study of Augusto de Campos’ translational poetics, departing from the opposition between constructivism and subjectivity. This corpus of translations is approached as undetachable from the author’s own poetical works. In these two fields of activity, as well as in his critical writings, Augusto de Campos advocates for an objective poetry - one that may be referred to as ‘constructive’ – in clear opposition to expressional lyricism, characterized by the affirmation of a Self. This research then examines how Augusto de Campos’ translational works, although being led by criteria refractory to subjective expression, may display subjective elements in its exercise of critical and creative translation, just as it raises questions concerning the very notion of subjectivity. Emphasis is set on translations from the works of e. e. cummings, Arnaut Daniel and Rainer Maria Rilke. Translations of other poets are also occasionally discussed as well as critical texts in which the author conveys his reflections about the task of translation, his criteria for selecting poets and his own idea of poetry in general.